2022
DOI: 10.12973/eu-jer.11.2.1209
|View full text |Cite
|
Sign up to set email alerts
|

X’s and Y’s in the Midst of the Pandemic: Generational Identity, Mental Well-being and Life Satisfaction Among Filipino Adult Learners

Ronnell D. Dela-Rosa,
Jerome V. Cleofas,
Ryan Michael F. Oducado

Abstract: <p style="text-align: justify;">The 2019 novel Coronavirus disease (COVID-19) has increased the mental health challenges and decreased the quality of life among students and the general adult population. However, adult learners and non-traditional students who are currently at their quarter and midlife during the pandemic, remain underrepresented in well-being research. Moreover, the unique sociocultural and historical contexts specific to generational cohorts may have an impact on the way they experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…This supports the diathesis-stress hypothesis during the pandemic, where young LGBTQ+ students experiencing lower life satisfaction and COVID-induced confinement and restrictions were more likely to have depression and low mental well-being in the post-quarantine period. This finding supports previous studies that indicate a cross-sectional relationship between life satisfaction and mental health (Dela-Rosa et al, 2022;Preetz et al, 2021;Rogowska et al, 2020). In particular, the present study revealed longitudinal data demonstrating how low improvement in life satisfaction throughout the two-year-long quarantine may lead to depression and low mental well-being in the post-quarantine period among young LGBTQ+ students.…”
Section: Discussionsupporting
confidence: 92%
“…This supports the diathesis-stress hypothesis during the pandemic, where young LGBTQ+ students experiencing lower life satisfaction and COVID-induced confinement and restrictions were more likely to have depression and low mental well-being in the post-quarantine period. This finding supports previous studies that indicate a cross-sectional relationship between life satisfaction and mental health (Dela-Rosa et al, 2022;Preetz et al, 2021;Rogowska et al, 2020). In particular, the present study revealed longitudinal data demonstrating how low improvement in life satisfaction throughout the two-year-long quarantine may lead to depression and low mental well-being in the post-quarantine period among young LGBTQ+ students.…”
Section: Discussionsupporting
confidence: 92%